Corporate Social Performance as a Business Strategy - Dentchev, Nikolay A. (Journal of business ethics, 2004)
Having the ambition to contribute to the practical value of the theory on corporate social performance (CSP), this paper approaches the question whether CSP can contribute to the competitive advantage of firms. We adopted an explorative case-study methodology to explore the variety of positive and negative effects of CSP on the competitiveness of organizations. As this study aimed at identifying as great variety of these effects as possible, we selected a diversified group of respondents. Data was thus collected through embedded units of analysis in a petrochemical company, and triangulated with the opinions of experts on CSP. Overall, we found various positive and negative effects of CSP on the competitiveness of organizations. CSP is therefore not an innocent adventure for executives, but rather a strategy for achieving corporate objectives. If not carefully implemented, the CSP strategy may harm the competitive advantage of the firm, as our results have suggested.